Relatedness in the Patterns of Interindustry Diversification - Lemelin, Andre (The Review of Economics and Statistics, 1982)
D ESPITE the abundance of literature on mergers, relatively little has been written specifically on the subject of diversification. Noteworthy exceptions are Gort (1962), Berry (1975), Caves (1975), Caves et al. (1977, 1980), and Hassid (1975). But regression analyses of outbound diversification have tended to yield unsatisfactory results, both in terms of the degree of significance of coefficients and in terms of overall explanatory power. In this paper I propose to consider diversification from a different point of view, by looking at patterns of diversification or, to be more specific, at pairs of origin-target industries. This approach emphasizes the role of a class of variables describing a relationship between origin and target industries. A number of such variables are specified, and some supporting empirical evidence is offered. The paper is organized as follows: section I gives definitions and presents the theoretical background; section II discusses the data; section III describes the specification; section IV analyzes the results; and section V summarizes findings.